Water quality indices as a tool for evaluating water quality and effects of land use in a tropical catchment - Simonetti, Vanessa C. [UNESP] (2019)
Human actions are degrading water quality, affecting the health of ecosystems and the availability of potable water for human consumption. Therefore, the monitoring of water systems is essential for recovery and management purposes. This study aimed to investigate the water quality in the environmental protection area (EPA) of Itupararanga Reservoir (Brazil) using water quality indices, pointing out land uses that contributing to the deterioration of water quality. The spatial analysis involved the creation of land use and soil maps of the sub-catchment areas of Itupararanga. Water quality index (WQI), trophic state index (TSI), aquatic life index (ALI), index of minimum variables for the maintenance of aquatic life (IMVMAL) and metals pollution potential index (MPPI) were calculated. The land uses which can affect the water quality on long term were identified. TSI (mesotrophic and hypereutrophic) and ALI showed results above the recommended values were. MPPI presented high values for the elements Al, Cr and Fe. Principal component analysis (PCA) showed spatial variability in the reservoir. In conclusion, the sampling sites with lower water quality were Sorocabuçu and Una, followed by Sorocamirim. These sites probably explain the deteriorated water quality found in sampling point Res1 of the reservoir for all indices analysed.